THE MOST PRESSING PROBLEM TODAY IS IODINE DEFICIENCY - Isaqova Nasiba Raxmatjonovna (Scholar Express Journals, 2023)
The article discusses iron deficiency anemia as an actual problem in medical practice. The authors of the article believe that the causes of iron deficiency first cause a decrease in its reserves in the macrophages of the liver, spleen and bone marrow, and then the concentration of iron in the blood. A negative iron balance develops, a manifestation of which is ALS. To prevent iron deficiency states it is necessary to effectively and promptly restore iron reserves in the body. Given the predominance of bread in the diet of the majority of the population, it is necessary to ensure the consumption of products (flour, flour products) enriched with iron preparations, combined with C vitaminization of the diet. In our opinion, this way of primary prevention of IDA is acceptable for city dwellers living in a difficult socio-economic situation.
Keywords: iron deficiency; chronic blood loss; esophageal hernia of the diaphragm